2016
DOI: 10.1371/journal.pone.0159281
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and History of the Lost SIV from Crab-Eating Macaques: SIVmfa

Abstract: In the 20th century, thirteen distinct human immunodeficiency viruses emerged following independent cross-species transmission events involving simian immunodeficiency viruses (SIV) from African primates. In the late 1900s, pathogenic SIV strains also emerged in the United Sates among captive Asian macaque species following their unintentional infection with SIV from African sooty mangabeys (SIVsmm). Since their discovery in the 1980s, SIVs from rhesus macaques (SIVmac) and pig-tailed macaques (SIVmne) have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The last group of SIV genomes with certain similar features consists of lineages smm, mac, mne and stm. SIVsmm infecting sooty mangabeys is the origin of HIV-2 and all these SIV lineages ( McCarthy et al. 2016 and refs therein; Sharp and Hahn 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…The last group of SIV genomes with certain similar features consists of lineages smm, mac, mne and stm. SIVsmm infecting sooty mangabeys is the origin of HIV-2 and all these SIV lineages ( McCarthy et al. 2016 and refs therein; Sharp and Hahn 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…HIV-2, comprising eight groups, originated following eight cross-species transmissions of SIVsmm from sooty mangabeys ( 72 76 ). Interestingly, SMs naturally infected with SIVsmm were the origin of the major reference strains in macaques ( 77 , 78 ), following accidental transmissions that occurred during kuru ( 79 ) and leprosy ( 80 ) experiments carried out in the 1970s in the National Primate Research Centers in the US ( 81 ). This accidental experimental transmission of these viruses (which involved serial passages) is probably the reason for their high pathogenicity in macaques ( 82 ).…”
Section: The Natural Hosts Of Sivs Are the Origin Of Pathogenic Sivs ...mentioning
confidence: 99%
“…Furthermore, studies have shown [22] that the same experiments carried out at the CNPRC were likely responsible for the infection of SIVs of different other species of macaques, such as the pigtailed macaques (Macaca nemestrina) [24] and the stumptailed macaque (Macaca arctoides) [25,26] and crab eating macaque (Macaca fascicularis) [27]. The progenitor viruses were from sooty mangabeys at the CNPRC which were used for kuru experiments, allowing for serial passaging and eventual establishment of the SIVmac239 and SIVmac251 isolates.…”
Section: You Can Call Me Siv: Introduction and The Origin Of Sivmacmentioning
confidence: 99%
“…Furthermore, studies have shown [22] that the same experiments carried out at the CNPRC were likely responsible for the infection of SIVs of different other species of macaques, such as the pigtailed macaques (Macaca nemestrina) [24] and the stumptailed macaque (Macaca arctoides) [25,26] and crab eating macaque (Macaca fascicularis) [27].…”
Section: You Can Call Me Siv: Introduction and The Origin Of Sivmacmentioning
confidence: 99%